International Baccalaureate in Japan and Asia - Ishikura, Yukiko (International Higher Education, 2018)
The International Baccalaureate (IB) offers internationally recognized programs that prepare students to think and act critically and independently as internationally competent individuals. IB has recently undergone a rapid worldwide expansion as an increasing number of educational systems are recognizing the value of nurturing globally prepared citizens. Japan, in particular, has witnessed a recent increase in the spread of IB programs because of the government-initiated push to increase the number of IB schools to 200 by 2020. The IB Dual Language Program (English and Japanese) was created to support this initiative. This article sheds light on the trend of IB expansion worldwide through the lens of the Japanese experience and addresses challenges and opportunities that this expansion has brought to Japanese higher education.